Handbook of Automotive Power Electronics and Motor Drives - Emadi Ali (Taylor & Francis, 2005)
Covering applications in conventional, hybrid-electric, and electric vehicles, this book provides a comprehensive reference for automotive electrical systems. This authoritative handbook features contributions from an outstanding international panel of experts from industry and academia, highlighting existing and emerging technologies. Divided into five parts, it offers an overview of automotive power systems, discusses semiconductor devices, sensors, and other components, explains different power electronic converters, examines electric machines and associated drives, and details various advanced electrical loads as well as battery technology for automobile applications.